2021
DOI: 10.3390/nano12010121
|View full text |Cite
|
Sign up to set email alerts
|

g-C3N4: Properties, Pore Modifications, and Photocatalytic Applications

Abstract: Graphitic carbon nitride (g-C3N4), as a polymeric semiconductor, is promising for ecological and economical photocatalytic applications because of its suitable electronic structures, together with the low cost, facile preparation, and metal-free feature. By modifying porous g-C3N4, its photoelectric behaviors could be facilitated with transport channels for photogenerated carriers, reactive substances, and abundant active sites for redox reactions, thus further improving photocatalytic performance. There are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 225 publications
(222 reference statements)
0
31
0
Order By: Relevance
“…One the one hand, the high photostability and non-toxicity of semiconductors and, on the other hand, the wide absorption range and low costs of organic dyes attracted great research interests for decades (Lang et al, 2014;Nalzala Thomas et al, 2021). However, the rapid recombination of photogenerated electron-hole pairs and the resulting low photoefficiency of semiconductors as well as the low photostability of organic dyes limit their applicability (Cao et al, 2015;Penu et al, 2015;Chen et al, 2018;Nalzala Thomas et al, 2021;Dong et al, 2022). Therefore, due to the tunable redox and excited state properties of transition-metal complexes, there is an intensive search for efficient and robust transition-metal based photosensitizers (Eckenhoff and Eisenberg, 2012;Frischmann et al, 2013;Berardi et al, 2014;Yuan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One the one hand, the high photostability and non-toxicity of semiconductors and, on the other hand, the wide absorption range and low costs of organic dyes attracted great research interests for decades (Lang et al, 2014;Nalzala Thomas et al, 2021). However, the rapid recombination of photogenerated electron-hole pairs and the resulting low photoefficiency of semiconductors as well as the low photostability of organic dyes limit their applicability (Cao et al, 2015;Penu et al, 2015;Chen et al, 2018;Nalzala Thomas et al, 2021;Dong et al, 2022). Therefore, due to the tunable redox and excited state properties of transition-metal complexes, there is an intensive search for efficient and robust transition-metal based photosensitizers (Eckenhoff and Eisenberg, 2012;Frischmann et al, 2013;Berardi et al, 2014;Yuan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that doping with noble metal ions optimized the photocatalytic performance according to several reports in the literature as a result of the higher separation of the photoproduced electrons and holes due to the excellent capacity of electron capture by the noble metallic ions [ 26 , 75 ]. A great deal of research is ongoing regarding g-C 3 N 4 modification for fabricating and designing nanomaterials with different properties in order to obtain the best possible photocatalytic performance for the removal of antibiotics [ 76 ].…”
Section: Common Photocatalytic Materials For Antibiotic Degradationmentioning
confidence: 99%
“…Nevertheless, various issues (including stability in the presence of solar light) may have crucial roles in the formation of newly designed nitrogen-rich polymeric carbon nitride photocatalysts. 14 Also, highly proficient solar light-harvesting ability and energy-transfer ability by dyes to a g-C 3 N 4 moiety are very important. 36 As a result, integration and selection of custom-made dye systems are needed while mounting these photocatalysts.…”
Section: Introductionmentioning
confidence: 99%